2016
DOI: 10.1007/s12032-016-0789-x
|View full text |Cite
|
Sign up to set email alerts
|

Dose to specific subregions of pelvic bone marrow defined with FDG-PET as a predictor of hematologic nadirs during concomitant chemoradiation in anal cancer patients

Abstract: To test the hypothesis that irradiated volume of specific subregions of pelvic active bone marrow as detected by (18)FDG-PET may be a predictor of decreased blood cells nadirs in anal cancer patients undergoing concurrent chemoradiation, we analyzed 44 patients submitted to IMRT and concurrent chemotherapy. Several bony structures were defined: pelvic and lumbar-sacral (LSBM), lower pelvis (LPBM) and iliac (IBM) bone marrow. Active BM was characterized employing (18)FDG-PET and characterized in all subregions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 27 publications
3
28
0
1
Order By: Relevance
“…The effect of chemoradiation is also apparent in the volumes of activeBM which were significantly reduced; iliac and lumbosacral activeBM showed a greater than 20% loss when expressed as a percentage of whole BM. The distribution of pelvic activeBM shown in this study is consistent with previous publications [16] with the majority located in iliac and lumbosacral bone. Only 23% was found in the lower pelvis, this combined with the fact lower pelvic bone receives a very high dose (V20 > 85%, the highest dose of any PBM sub structure) would indicate the significance of any sparing of lower pelvic bone on rates of haematological toxicity can be largely discounted.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The effect of chemoradiation is also apparent in the volumes of activeBM which were significantly reduced; iliac and lumbosacral activeBM showed a greater than 20% loss when expressed as a percentage of whole BM. The distribution of pelvic activeBM shown in this study is consistent with previous publications [16] with the majority located in iliac and lumbosacral bone. Only 23% was found in the lower pelvis, this combined with the fact lower pelvic bone receives a very high dose (V20 > 85%, the highest dose of any PBM sub structure) would indicate the significance of any sparing of lower pelvic bone on rates of haematological toxicity can be largely discounted.…”
Section: Discussionsupporting
confidence: 92%
“…The main limitation of this work is a relatively small sample size, subsequently whilst we have attempted to quantify the relationship between dose to activeBM and blood count nadir this should be strongly viewed in the context of the small sample size, larger studies are required. Additionally, whilst the definition of activeBM as that greater than the mean SUV seen in an individual patients whole PBM is used here and elsewhere in literature [16] this is largely a pragmatic arbitrary threshold rather than one based on physiology.…”
Section: Discussionmentioning
confidence: 99%
“…The lumbosacral spine has been found to have the highest region of active bone marrow within the pelvis [17], and the V40 of the lumbosacral spine has been shown to be strong predictor of grade 3þ hematologic toxicity [15]. However, Rose et al [18] has demonstrated that radiation doses to the total pelvic bone marrow, lumbosacral bone marrow, and iliac bone marrow are all individually associated with hematologic toxicity and therefore sparing just a portion of the pelvic bone marrow may be insufficient to decrease bone marrow suppression.…”
Section: Discussionmentioning
confidence: 99%
“…18 F-FDG-PET has been used to identify areas of metabolically active bone marrow. Franco et al [17] demonstrated that areas of active bone marrow significantly correlate with white blood cell count, absolute neutrophil count, and platelet nadirs. Further work is needed to define the optimal SUV parameters to segregate an active marrow subsite and it is uncertain whether this is a better dosimetric predictor of hematologic toxicity compared with total bone.…”
Section: Discussionmentioning
confidence: 99%
“…To help lower this risk, dosimetric parameters to reduce hematologic toxicity (HT) have been investigated. Mell et al first reported on V10 and V20 of pelvic bone marrow (PBM) being associated with acute leukopenia and neutropenia in patients with AC and subsequent studies have shown similar results [6][7][8][9][10][11][12]. Recent studies suggest that BM, much like the liver, is a parallel organ and the volume spared a threshold dose may better predict acute HT [10,13].…”
Section: Introductionmentioning
confidence: 96%